Reaching the hard to reach: quantitative and qualitative evaluation of school-based arts therapies with young people with social, emotional and behavioural difficulties. Issue 4 (1st October 2016) - Cobbett, Steve
ABSTRACT: The arts therapies are becoming more commonplace as psychotherapeutic interventions for young people with social, emotional and behavioural difficulties (SEBD) and associated mental health conditions in educational settings and are now used in many educational provisions. The justification for their use would seem to be largely based on the subjective experience of education managers and anecdotal evidence as empirical evidence for their effectiveness with this client group is scarce. This research article is an attempt to fill that gap. A sample of 52 young people receiving an arts therapy and a control sample of 29 young people on a waiting list for an arts therapy were assessed over a year-long period in two SEBD schools in London using staff-rated Goodman's Strengths and Difficulties Questionnaires (SDQ) and a self-rated scoring system. SDQ results showed a significant difference in improvement of levels of SEBD compared to the control group across all measures with emotional and conduct difficulties showing a large effect. Three out of four self-rated score categories also showed significant difference in improvement compared to the control group. The quantitative data were supplemented with qualitative data obtained via interviews with six young people who had received an arts therapy. The data were analysed using Interpretative Phenomenological Analysis (IPA). Themes emerging from this data suggested that young people felt that the arts brought various benefits to their therapy that augmented the verbal side and helped them to engage in therapy.